2019
DOI: 10.1002/aenm.201901341
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐Generated Nanocrystals in Perovskite: Universal Embedding of Ligand‐Free and Sub‐10 nm Nanocrystals in Solution‐Processed Metal Halide Perovskite Films for Effectively Modulated Optoelectronic Performance

Abstract: Regulating the chemical/physical features of solution processed metal halide perovskite films by integrating sub‐10 nm nanocrystals is a highly promising strategy to advance their outstanding optoelectronic performance. However, significant challenges remain for the universal embedding of the well‐defined nanocrystals in the film matrix. By generating nanocrystals in desired solvents via pulsed laser irradiation in liquid, the authors demonstrate the effective decoration of sub‐10 nm nanocrystals in perovskite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 52 publications
(113 reference statements)
0
32
0
Order By: Relevance
“…The distribution of the oligomer can be observed through the cross-sectional backscattered scanning electron (BSE) imaging due to the atomic number difference reflected by strength of backscattered electron signals. [33] It can be depicted from Figure 1b that distinct black regions are separately dispersed throughout the entire layer if comparing to that of control layer (Figure S2, Supporting Information). Energy dispersive X-ray spectroscopy in the cross-sectional SEM (SEM-EDS) observations (Figure 1c) reveals distribution of F and Si elements (characteristic elements in PFTS) in the entire perovskite layer (according to the Pb element distribution).…”
Section: Resultsmentioning
confidence: 93%
“…The distribution of the oligomer can be observed through the cross-sectional backscattered scanning electron (BSE) imaging due to the atomic number difference reflected by strength of backscattered electron signals. [33] It can be depicted from Figure 1b that distinct black regions are separately dispersed throughout the entire layer if comparing to that of control layer (Figure S2, Supporting Information). Energy dispersive X-ray spectroscopy in the cross-sectional SEM (SEM-EDS) observations (Figure 1c) reveals distribution of F and Si elements (characteristic elements in PFTS) in the entire perovskite layer (according to the Pb element distribution).…”
Section: Resultsmentioning
confidence: 93%
“…Surface modification with various catalytic and non‐catalytic materials was shown to be an effective strategy to improve the performance of hematite 13,65 . In addition, lattice mismatch or Schottky contact at hematite/substrate interface may result in the formation of Fermi level pinning 66 and energy barrier, 60,67 which are infavorable for the carriers separation and transport.…”
Section: Overview Of Hematitementioning
confidence: 99%
“…Fortunately, several recent studies have reported that additive engineering is an effective alternative strategy. Various additives, such as polymers, small molecules, and semiconductor molecules, have been incorporated into perovskite precursor solutions . Although additives containing N, O, and S atoms with lone pairs of electrons were found to be efficient in passivating defects in perovskite films and further enhanced charge transfer and collection, they lacked sufficient evidence to demonstrate that the defect passivation undoubtedly occurred at GBs .…”
Section: Introductionmentioning
confidence: 99%